Glycohemoglobin: A new warning strategy for non-alcoholic fatty liver disease: Study from the NHANES 2017- 2020 - Hou, Jiaxing; Liu, Yanyu; Deng, Zhen; Sun, Jichun; Zhao, Mingyi (Frontiers in Endocrinology, 2022)
Context: The development and progression of Non-alcoholic Fatty Liver Disease (NAFLD) is associated with type 2 diabetes mellitus (T2DM), but there are no studies to demonstrate whether blood glucose levels are associated with the progression of NAFLD. Objective: Alterations in glucose metabolism may cause hepatic steatosis and inflammatory responses, leading to hepatocyte damage and promoting NAFLD's progression. Since glycohemoglobin reflects current blood glucose levels and is easily detectable, the present study aimed to investigate whether glycohemoglobin is associated with liver stiffness in patients with NAFLD. Methods: We studied 1510 NAFLD patients aged 20-80 in NHANES 2017- March 2020, who were defined using the Controlled attenuation parameter (CAP) ≥263 dB/m. Multivariable linear regressions were used to assess the independent association between glycohemoglobin and median liver stiffness measurements (LSM) after adjusting for potential confounders. Subsequently, they were subjected to curve fitting and threshold effect analysis. Stratified analysis was used to find the variables affecting the relationship. Results: Glycohemoglobin and median LSM showed a positive correlation in different models (β (95% CI): Crude Model: 1.460 (1.053, 1.867); Model 1: 1.476 (1.066, 1.885); Model 2: 1.517 (0.919, 2.115)), and this correlation disappeared when glycohemoglobin ≥8.6%. Furthermore, this correlation was more pronounced in the non-diabetic and former smoking subgroups. Conclusion: In patients with NAFLD, glycohemoglobin may reflect the degree of liver stiffness, and preventing excessive glycohemoglobin may have a positive effect on slowing the progression of NAFLD especially in non-diabetic and former smokers.